HUBUNGAN FUNGSI DAN TATA KERJA DEWAN PERWAKILAN RAKYAT DAERAH DENGAN BUPATI MENURUT UNDANG UNDANG NOMOR 32 TAHUN 2004 (Studi di Kabupaten Sumbawa Barat) - Linayati Lestari (Universitas Riau Kepulauan, 2015)
ABSTRACTThe purpose of this study was to determine the grounding normative functional in relation to the workings of Parliament with the Regent, the mechanism of relations functions and Working Procedure of the Regional Representatives Council with the Regional Head in the local government system in accordance with Law No. 32 of 2004, as well as menetahui factors affect the functioning and working procedures of Parliament with the Regional Head of governance in the region of West Sumbawa regency. Problems of law functions in relation to the working procedures of the Regional Representatives Council (hereinafter abbreviated DPRD) with Regent interesting to study. It concerns the functional normative grounding in the workings of Parliament relations with the Regent, the mechanism of structural-function relationships work procedures, as well as the factors that influence it. Basically the function of the relationship between the workings of Parliament with the Regents set forth in Article 41 of Law Number 32 Year 2004 on Regional Government, which states: Parliament has a legislative function, budgeting, and oversight. This relationship continues to change.The approach taken in this study is the first is a normative approach, it is oriented as the workings of Parliament relations with the Regent based on the rule of law. With regard to the approach taken, are: (statute approach) the approach through the fundamental role assumed by local institutions is carried out according to the function and the main task; in addition, used the conceptual approach which is done in this approach explains the concept in accordance with the current state (conseptual approach). Then the second is: the law of the empirical approach (Socio-legal approach) that is the approach that examines the law in reality.Results of this study that the association functions and working procedures of the Parliament with the Regional Head both in Law No. 22 of 1999 and Law of the Republic of Indonesia Number 32 Year 2004 on Regional Government is the same that includes relations legislation, elections, budgets, accountability, oversight , administration, initiatives and aspirations of the people. But the Law of the Republic of Indonesia Number 32 of 2004 on regional governance, providing opportunities in the implementation of the regional administration in the